Analisis Daya Saing Daerah Kabupaten/Kota di Sumatera Barat Berdasarkan Pilar Daya Saing - Shabrina, Alyani Kinasih Nur; Riani, Novya Zulva; Akbar, Urmatul Uska (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
The purpose of this study is to analyze and classify the level of competitiveness of districts/cities in West Sumatra. This research uses secondary data sourced from the Central Statistics Agency (BPS) and the National Research and Innovation Agency (BRIN) for 2022-2023. This research uses RCI (The European Regional Competitiveness Index) calculation and Klassen Typology analysis. Based on the research results, it is found that each pillar supports each other and is closely related to economic growth. Some areas in West Sumatra, especially remote areas such as Mentawai Islands, suffer from lack of infrastructure such as roads, electricity, and public facilities. Major cities such as Padang are often the center of infrastructure development, while other districts are given less attention. There is a disparity in macroeconomic stability among districts and cities in West Sumatra.